Effects of immunosterilization on body weight gain, carcass yield and fleece weight in young Junín rams - Unchupaico P., Ide (2018)
The aim of the study was to evaluate the effect of immune sterilization on body weight gain, carcass yield and fleece weight in Junin sheep by applying an anti-GnRH synthetic protein. The study was conducted at the SAIS "Tupac Amaru", Junin, Peru, at an altitude of 3587 m between September and December 2017. Eighty 11-13-month-old rams were used and randomly distributed into four treatments (20 per group). Treatments were T1: surgical castration, T2 and T3: application of 0.5 and 1.0 ml of anti-GnRH vaccine, and T4: control (application of a placebo). For the immune sterilization, two doses of Improvac® were subcutaneously applied in the axillary region at 21-day intervals. Body weight was taken every 15 days for three months and the weight of dirty fleece was taken immediately after shearing. The results show that the application of anti-GnRH vaccine at a dose of 1.0 ml improvement increases daily body weight gain and the final body weight (p<0.05), while for carcass yield and fleece weight no significant differences were found between treatments. It is concluded that the application of the anti-GnRH vaccine in sheep improves the productive performance of these animals.